1988
DOI: 10.1159/000242865
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Insulin with Small Intestinal Epithelial Cells from Developing Rats

Abstract: The interaction of insulin with its specific receptors was studied in jejunoileal epithelial cells from 14-, 20-, and 60-day-old rats. Characteristics such as potency and specificity of the insulin receptor system did not vary during development. However, insulin binding decreased with age due to a diminished concentration of insulin receptors, whereas the circulating levels of the hormone followed an inverse evolution. These results support previous suggestions on the potential role of insulin on the mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Radioligand binding experiments have documented the presence of IRs in fetal, suckling, weaning and adult mammal enterocytes (18‐20). In the rat small intestine, IRs were found on both the jejunal and ileal brush border surfaces (18,21), and the specific binding of 125 I insulin to the IRs was found to be 2 times higher in the ileum compared with the jejunum (22). Moreover, in that study (22), it was shown that preferential localization of insulin‐binding sites to the intestinal crypt cells regardless of the age of the animal and certain cell types in the intestinal mucosa express specific substrates of apparent similar molecular mass (60‐kDa) that assume different functions in the IR signal transduction pathways (22).…”
Section: Local Effects On the Gastrointestinal Tractmentioning
confidence: 99%
See 1 more Smart Citation
“…Radioligand binding experiments have documented the presence of IRs in fetal, suckling, weaning and adult mammal enterocytes (18‐20). In the rat small intestine, IRs were found on both the jejunal and ileal brush border surfaces (18,21), and the specific binding of 125 I insulin to the IRs was found to be 2 times higher in the ileum compared with the jejunum (22). Moreover, in that study (22), it was shown that preferential localization of insulin‐binding sites to the intestinal crypt cells regardless of the age of the animal and certain cell types in the intestinal mucosa express specific substrates of apparent similar molecular mass (60‐kDa) that assume different functions in the IR signal transduction pathways (22).…”
Section: Local Effects On the Gastrointestinal Tractmentioning
confidence: 99%
“…Radioligand binding experiments have documented the presence of IRs in fetal, suckling, weaning and adult mammal enterocytes (18‐20). In the rat small intestine, IRs were found on both the jejunal and ileal brush border surfaces (18,21), and the specific binding of 125 I insulin to the IRs was found to be 2 times higher in the ileum compared with the jejunum (22).…”
Section: Local Effects On the Gastrointestinal Tractmentioning
confidence: 99%
“…In support of this theory, insulin receptors have been detected in the small intestine of fetuses, newborn, and suckling rats (19), and their concentration peaks at the end of the suckling period (19,20). In addition, we have shown (20) that both α‐ and β‐subunits of the insulin receptors are equally concentrated in BBM and in basolateral membranes of villus and crypt cells (20).…”
Section: Discussionmentioning
confidence: 89%
“…Alterations in insulin receptor activity have been reported in models that would induce intestinal hyperplasia. The affinity, but not the binding capacity, of insulin receptors decreased in crypt cells, but not in mature villous cells after small bowel resection (Fernandez-Moreno, Arilla & Prieto, 1986;Fernandez-Moreno, Fernandez-Gonzalez, Diaz-Juarez, Lopez-Luna & Prieto, 1988).…”
Section: Discussionmentioning
confidence: 99%